Influence of the Mentis Plus+ program on the mental health of university students from a public university in Puno, Peru - Incacutipa-Limachi, Duverly Joao; Velasquez-Velasquez, Vilma; Esteves-Villanueva, Angela Rosario; Sucapuca-Cancapa, Anny (Journal of Ecohumanism, 2024)
The purpose of the study is to determine the influence of the Mentis Plus+ program on the mental health of Anthropology university students at the National University of Altiplano, Puno in Peru. The research was carried out using a quantitative approach with an experimental design, employing a pretest and a posttest. The Positive Mental Health Program for adults was implemented, based on the Lluch Multifactorial Model of Positive Mental Health. The participants were 60 students, divided into an experimental group and a control group, each with 30 participants. The group sessions were implemented systematically and developed over 8 weeks. In the results, before the intervention, both groups, Experimental (E) and Control (C), were in equivalent conditions corroborated with the Mann Whitney U test. After the application of the program, group E showed significant improvements in all dimensions, reaching "Medium" and "High" levels (p = 0.000). In contrast, group C did not show improvements and experienced deteriorations in some dimensions, such as prosocial attitude and self-control. In conclusion, the intervention significantly improved the mental health of the experimental group, while the control group maintained a high prevalence at low levels. These differences underline the positive impact of the Mentis Plus+ program on the mental health of university students.